Determination of Clarithromycin and its Applications in Pharmaceutical Samples Using New Selective Electrodes - Sarra A. Abrahem (Journal of Global Pharma Technology, 2019)
Two clarithromycin electrodes were constructed using clarithromycin-methyl orange as an ion pair complex in a Polyvinyl-chloride (PVC) matrix. These electrodes were plasticized using two plasticizers, Acetophenone (AP) and Di-butyl phosphate (DBP).Clarithromycin electrodes, a and b, gave slopes of 53.95 and 51.50mV/decade, and linear which ranged from (10-4-10-1, and 6×10-4-10-1 M) respectively. Electrode (a) relied on using a plasticizer (DBP) of a slope 53.95mV/decade, and a correlation coefficient 0.9996, with a detection limit of 5x10-5M in a lifetime of 26 days. The proposed electrode showed reproducibility and a good stability. It was therefore employed for determining clarithromycin within pharmaceutical samples. The measurements of interferences in the availability of (Na+, Cu+2, K+, Mn+2, Al+3, Fe+3, gelatin and sucrose) were also studied for selectivity coefficient determination using the separation method and the mixed method.Keywords: Clarithromycin, Methyl orange, Ion selective electrode.